(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted with different Basmati rice varieties at the Bangladesh Rice Research Institute (BRRI) farm, Gazipur during 1999 and 2000 T.aman season. Four rice genotypes (Basmati PNR, Basmati 370, Basmati 375 and Basmati-D) were tested with 0, 25, 50, 75 and 100 kg N/ha to determine the optimum N level as well as to find out the genotype having high yield potential. The plant height, tiller number, number of panicles, panicle length, spikelet sterility and straw yield increased with the increase of nitrogen levels upto 75 kg N/ha. Maximum plant growth at the highest level of N caused lodging of plant which increased spikelet sterility and lower number of grains per panicle and ultimately decreased grain yield. Genotype Basmati PNR having dwarf plant characteristics performed well at higher level of nitrogen (100 kg N/ha), while other genotypes having medium plant height responded well at lower level of nitrogen (52-56 kg N/ha). Keywords: Basmati rice; nitrogen; aman season. DOI: 10.3329/bjar.v35i1.5877 Bangladesh J. Agril. Res. 35(1) : 157-165, March 2010